P-015 Initial experience with a coaxial dual-lumen balloon catheter for wide-neck aneurysm coil embolization. (12th July 2011) - Lazzaro, M; Zaidat, O; Badruddin, A; Fitzsimmons, B
Abstract : Introduction: Techniques for coil-embolization of wide-neck cerebral aneurysms include the use of stents and temporary occlusion with compliant non-detachable balloons to achieve safe and densely packed coil positioning. We describe the use of a new balloon device for wide-neck aneurysm treatment. Methods: A single institution neuroendovascular device inventory was accessed to identify cases in which the Ascent balloon (Micrus Endovascular, San Jose, California, USA) was used for aneurysm coil embolization. Clinical, demographic, and angiographic data were obtained through chart review. Results: Six cerebral aneurysm cases were treated using the Ascent balloon during the first 8-month period that the new device was available at our institution. Two of the patients presented with ruptured aneurysms. All aneurysms were large (maximum diameter 7 mm or greater) with an average neck length of 6.1 mm. Complete occlusion with coil embolization (Raymond class I) was achieved in all cases. The Ascent balloon was successfully positioned across the neck of the aneurysm in five patients, while delivery to the aneurysm neck was unsuccessful due to vessel tortuosity in one patient. Conclusions: This initial experience demonstrates the feasibility, initial outcomes, and short-term follow-up results of a coaxial dual-lumen design balloon catheter used as an assistive device in coil embolization of wide-neck cerebral aneurysms. This new device contributes to the growing number of options for treatment of complex cerebral aneurysms.